Impact of eigenvalues on the electron-phonon coupling strength of aluminium and its binary alloys - Kantha, B. K.; Chakrabarti, S. K.; Jha, I. S.; Singh, B. P. (BIBECHANA, 2014)
Aluminium is a third group element according to the periodic table. Chemically it is a reactive metal often forming complexes within its binary alloys. In the present work we have dealt with the impact of eigenvalues on the superconducting state parameter viz. the electron-phonon coupling strength of this metal. We have also dealt with the same for two binary alloys of it viz. aluminium-magnesium and aluminium-zinc. For this purpose we have computed the non-local screened form factor for each of them. Initially the orthogonalised plane wave parameter has been taken as unity. Thereafter Vashishta-Singwi form of exchange and correlation is employed. The core energy eigenvalues of Herman-Skillman have been used. Our results are quite satisfactory for the metal as well as its present alloys. Our computation reveals that the superconducting state parameter can be reasonably reproduced by Harrison’s first principle pseudopotential technique along with McMillan’s formalism provided a proper choice of the core energy eigenvalues is made. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11699 BIBECHANA 12 (2015) 35-39